INCREASING STUDENT LEARNING ACTIVITY THROUGH JIGSAW-TYPE COOPERATIVE LEARNING MODEL IN SCIENCE LEARNING AT MTs DARUL HIKAM - Mega Soimah; Feerlie Moonthana Indhra; Yurnalima Dewi (Scientechno: Journal of Science and Technology, 2026)
This research is motivated by the low learning activity of students in science learning at MTs Darul Hikam which is shown by the dominance of the use of conventional methods centered on teachers, so that students are less involved in asking questions, discussing, answering questions, and expressing opinions. This research aims to increase student learning activity through the application of the Jigsaw-type Cooperative Learning model in science learning. The method used is Classroom Action Research with a two-cycle design, and each cycle includes the stages of planning, implementation of actions, observation, and reflection. The subjects of the study were 25 students of class VIII C MTs Darul Hikam, while the data were collected through observation, interviews, documentation, and questionnaires, then analyzed qualitatively and quantitatively. The results showed that students' learning activity gradually increased from 38.83 percent in the first cycle of the first meeting to 54.67 percent in the second meeting, then increased again to 80.3 percent in the second cycle of the first meeting, and reached 91.83 percent in the second meeting. In conclusion, the application of the Jigsaw model is effective in increasing students' learning activity in science learning. The novelty of this research lies in the focus on measuring multidimensional learning activity in the context of madrasah tsanawiyah, while the implications show that the Jigsaw model is feasible to be applied as an innovative strategy to create more participatory, collaborative, and meaningful science learning